2003
DOI: 10.1007/bf02931372
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide alleviates oxidative damage in the green algaChlorella pyrenoidosa caused by UV-B radiation

Abstract: The effect of ultraviolet-B radiation (UV-B; 280-320 nm) on induction of nitric oxide was estimated in the suspensions of green alga Chlorella pyrenoidosa with or without the NO scavenger N-acetyl-L-cysteine, and reductants such as 1,4-dithiothreitol, glutathione (reduced form), and ascorbic acid. Exogenously added sodium nitroprusside (NO donor), glutathione, 1,4-dithiothreitol, and ascorbic acid were able to prevent chlorophyll loss mediated by UV-B. Addition of NO to algal suspensions irradiated by UV-B inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…A different response of catalase to UV-B has been reported in Nicotiana plumbaginifolia (Willekens et al 1994) and Zea mays (Boldt & Scandalios 1997) due to the presence of several isoforms and to the different metabolic functions. It has already been demonstrated that UV-B treatment can trigger upregulation of antioxidant enzymes (Chen et al 2003). Studies conducted by Yannarelli et al (2006) in soybean showed an increase of CAT activity under the lower UV-B doses demonstrating that this enzyme is up-regulated to safeguard normal cellular functions and survival.…”
Section: Discussionmentioning
confidence: 97%
“…A different response of catalase to UV-B has been reported in Nicotiana plumbaginifolia (Willekens et al 1994) and Zea mays (Boldt & Scandalios 1997) due to the presence of several isoforms and to the different metabolic functions. It has already been demonstrated that UV-B treatment can trigger upregulation of antioxidant enzymes (Chen et al 2003). Studies conducted by Yannarelli et al (2006) in soybean showed an increase of CAT activity under the lower UV-B doses demonstrating that this enzyme is up-regulated to safeguard normal cellular functions and survival.…”
Section: Discussionmentioning
confidence: 97%
“…With regard to algae, it was found that both exogenous and endogenous nitric oxide can alleviate oxidative damage in the green alga Chlorella pyrenoidosa caused by UV-B radiation (Chen et al, 2003a). Research indicated that exogenous antioxidants including ASC, NAC, and SNP can protect algae under UV-B radiation (Chen et al, 2003a), but, with regard to the roles of exogenous antioxidants on the response to oxidant stress, there is also little information, especially about how they interact with endogenous antioxidant enzymes to protect organisms from oxidant stress (He and Ha¨der, 2002a;Laspina et al, 2005;Malanga et al, 1999;Morley et al, 2003). In this study, these issues were investigated with aims to: (1) investigate the responses of photosynthesis and antioxidant enzymes of desert Nostoc sp.…”
Section: Introductionmentioning
confidence: 99%
“…In algae NO formation was reported to be involved in phototaxis (39) and stress responses (10,41), and in fungi it is related to processes such as growth (40,63) and formation of fruiting bodies (59).…”
mentioning
confidence: 99%